Nutritional Profile of Phytococktail from Trans-Himalayan Plants - Dhar, Priyanka; Tayade, Amol B.; Kumar, Jatinder; Chaurasia, Om P.; Srivastava, Ravi B.; Singh, Shashi B. (PLOS ONE, 2013)
We estimated the nutritive value, vitamin content, amino acid composition, fatty acid content, and mineral profile of a phytococktail comprising sea buckthorn (Hippophae rhamnoides), apricot (Prunus armeniaca), and roseroot (Rhodiola imbricata) from trans-Himalaya. The free vitamin forms in the phytococktail were determined by rapid resolution liquid chromatography/tandem mass spectrometry (RRLC-MS/MS). Vitamin E and B-complex vitamins were detected as the principle vitamins. Reversed-phase high performance liquid chromatography (RP-HPLC) with pre-column derivatization was used for identification and quantification of amino acids. Eight essential and eleven non-essential amino acids were quantified, and the content ranged between 76.33 and 9485.67 µg/g. Among the essential amino acids, L-methionine, L-phenylalanine, L-lysine, L-leucine, and L-histidine were found to be the dominant contributors. We also quantified the fatty acids in the phytococktail by using gas chromatography coupled with a flame ionization detector (GC-FID) with fatty acid methyl esters (FAMEs) derivatization. The analysis revealed the presence of 4 major fatty acids contributing to the total lipid content. Palmitic acid was found to be the rich source of saturated fatty acid (SFA) and constituted ∼31% of the total lipid content. Among the unsaturated fatty acids (UFAs), palmitoleic acid (43.47%), oleic acid (20.89%), and linoleic acid (4.31%) were prominent. The mineral profiling was carried out by inductively coupled plasma optical emission spectrometer (ICP-OES), and it was found to contain a number of important dietary mineral elements. The harsh climatic conditions, difficult terrain, and logistic constraints at high altitude regions of Indian trans-Himalayan cold desert lead to the scarcity of fresh fruits and vegetables. Therefore, the source of multiple vitamins, essential amino acids, fatty acids, and dietary minerals from the phytococktail would provide great health benefit in the stressful environment and could be used as a high value nutritional supplement.